2015
DOI: 10.1097/jcp.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Haloperidol, Amisulpride, and Quetiapine on Bone Turnover Markers in Patients With Schizophrenia

Abstract: The PRL-raising antipsychotic drug amisulpride influenced bone turnover balance very early in the course of treatment, which may require long-term monitoring of bone metabolism. Bone resorption marker changes induced by acute antipsychotic drug treatment are likely related to increased PRL levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Though no previous data have been published with regard to collagen alpha-1 (II) and collagen alpha-2 (I) chains in schizophrenia, Doknic et al [44] reported that a potential long-term consequence of asymptomatic hypogonadism due to risperidone-induced hyperprolactinemia may cause a slight rise in the C-terminal telopeptide of type I collagen (CTX), particularly in patients with schizophrenia who have been treated with long-acting injectable risperidone (LAIR) for 12 to 24 months. Liang et al [45] also reported significantly increased levels of the amisulpride group in patients with schizophrenia after 4 weeks of antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Though no previous data have been published with regard to collagen alpha-1 (II) and collagen alpha-2 (I) chains in schizophrenia, Doknic et al [44] reported that a potential long-term consequence of asymptomatic hypogonadism due to risperidone-induced hyperprolactinemia may cause a slight rise in the C-terminal telopeptide of type I collagen (CTX), particularly in patients with schizophrenia who have been treated with long-acting injectable risperidone (LAIR) for 12 to 24 months. Liang et al [45] also reported significantly increased levels of the amisulpride group in patients with schizophrenia after 4 weeks of antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have not consistently reported associations between bone mineral density (BMD) and prolactin levels in antipsychotic-treated patients (5), antipsychotic-induced hyperprolactinaemia has been suggested a causal factor underlying osteoporosis (6). BMD is commonly assessed by dual-energy X-ray absorptiometry (DXA).…”
Section: Introductionmentioning
confidence: 99%